2011
DOI: 10.1016/j.bbadis.2011.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Cilium, centrosome and cell cycle regulation in polycystic kidney disease

Abstract: Polycystic kidney disease is the defining condition of a group of common life-threatening genetic disorders characterized by the bilateral formation and progressive expansion of renal cysts that lead to end stage kidney disease. Although a large body of information has been acquired in the past years about the cellular functions that characterize the cystic cells, the mechanism(s) triggering the cystogenic conversion are just starting to emerge. Recent findings link defects in ciliary functions, planar cell po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 147 publications
(148 reference statements)
1
25
0
2
Order By: Relevance
“…2 D ) uses phylogenetic profiles as part of its prediction score, which should be correlated with MMM scores, this approach is only used for their prediction of bacterial protein interactions. HumanNet (Lee et al 2011) includes phylogenetic profiling as part of their prediction approach, and as expected, those scores are higher for gene pairs in the MMM12+ network (fig. 2 E ).…”
Section: Resultssupporting
confidence: 69%
“…2 D ) uses phylogenetic profiles as part of its prediction score, which should be correlated with MMM scores, this approach is only used for their prediction of bacterial protein interactions. HumanNet (Lee et al 2011) includes phylogenetic profiling as part of their prediction approach, and as expected, those scores are higher for gene pairs in the MMM12+ network (fig. 2 E ).…”
Section: Resultssupporting
confidence: 69%
“…Centrosome aberrations are associated with renal cystic disease [2], but a causative role for centrosome defects in cystogenesis has not been established. We speculate that the ciliary signaling defects in super-ciliated cells might play a role in the initiation of cyst formation.…”
Section: Resultsmentioning
confidence: 99%
“…Signaling molecules for cilium-associated pathways are concentrated in the cilium, and this is essential for efficient signaling. Cilia are nucleated from centrioles, and aberrant centriole numbers are seen in many cancers and in some ciliopathies [2]. We tested the effect of supernumerary centrioles on cilium function, and found that cells with extra centrioles often formed more than one cilium, had reduced ciliary concentration of Smoothened in response to Sonic hedgehog stimulation, and reduced Shh pathway transcriptional activation.…”
mentioning
confidence: 99%
“…There is a direct link between cilia, centrosomes and cell cycle dysregulation in PKD as reviewed in refs. 37 and 38. Through use of the CDK inhibitor R-roscovitine, we have recently shown that treatment of jck and cpk mice with slowly progressive and aggressive forms of PKD, respectively, resulted in a striking inhibition of cystic disease and improvement of renal function 29 .…”
Section: Discussionmentioning
confidence: 99%